2019
DOI: 10.1001/jamanetworkopen.2019.5536
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Risk Factors, and Mortality Associated With Second Malignant Neoplasms Among Survivors of Adolescent and Young Adult Cancer

Abstract: Key Points Question What are the incidence patterns and risk factors for second malignant neoplasms (SMN) among survivors of adolescent and young adult cancer? Findings This cohort study of 10 574 survivors of adolescent and young adult cancer found that these individuals had a 2.6-fold greater risk of developing SMN compared with individuals with no history of cancer. Risk factors for SMN included demographic factors, stage at diagnosis, and radiation ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 34 publications
(38 reference statements)
4
44
0
Order By: Relevance
“…To the best of our knowledge, this was the largest sample size study from a single medical center. Consistent with most previous studies ( 22 , 31 ), our findings provide evidence to support that worse OS is more common in pediatric patients with salivary MEC if the patient has a previous cancer history. The importance of long-term surveillance in cancer survivors must be emphasized.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…To the best of our knowledge, this was the largest sample size study from a single medical center. Consistent with most previous studies ( 22 , 31 ), our findings provide evidence to support that worse OS is more common in pediatric patients with salivary MEC if the patient has a previous cancer history. The importance of long-term surveillance in cancer survivors must be emphasized.…”
Section: Discussionsupporting
confidence: 92%
“…Keegan et al ( 30 ) found that a previous cancer history was associated with a worse prognosis in patients with Hodgkin lymphoma, sarcoma, or breast, thyroid, or testicular cancers. A similar finding was also reported by Chao et al ( 22 ); moreover, recently, Goldfarb et al ( 31 ) noted that a longer latency time (>5 years) suggested an overall increased risk of death. However, none of these studies enrolled patients with head and neck MEC.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…An increasing body of evidence indicates that tumors in AYAs are molecularly distinct from those in both younger and older age groups, possibly suggesting differences in etiology and effective treatment. [2][3][4] In addition, compared with older patients with cancer, AYAs have a higher risk of long-term and late effects, including infertility, sexual dysfunction, cardiovascular disease, and future cancers, [5][6][7][8] whereas compared with childhood cancer survivors, the risk of severe late effects is lower. 9 AYAs are also more likely than older patients with cancer to experience delays in diagnosis for some cancers because of higher uninsured rates, a lack of cost-effective early detection methods, and the rarity of cancer at this age.…”
Section: Introductionmentioning
confidence: 99%